Pemodelan Perilaku Dinamik Motor Induksi Tiga Fasa - Ahyanuardi, Ahyanuardi (Sainstek, 2008)
Dynamic performance induction motor had been need to analyze behavior induction motor except steady-state. The paper presents an investigation of transient performance of a three-phase squirrel-cage rotor induction motor. The underlying model technique chooses the stator and rotor d-q axis magnetic flux linkages as the state space variables.Â  The simulation of transient performance of the machine is examined for the starting process, and suddenly load. Typical results of the transient simulation are presented to suggest guidelines for really protection and control design problem identification of a squirrel-cage rotor three-phase induction motor. Key words: dinamic performance, transient performance, induction motor